Investigating different dimensions of sleep quality in medical university students - farahnaz kalantar mehrjardi; zahra sepehrmanesh; seyyed alireza moraveji (طب کار)
Introduction: Sleep is one of the most important circadian cycles and a complex biological pattern. Sleep and sleep disorders are crucial factors in the lives of individuals within society. The rate of sleep disorders is rising among individuals in society, especially among the youth. Some groups, such as students, have more sleep problems. The aim of this study was to investigate the quality of sleep among students. Materials and Methods: This case-control study was conducted on students living in the dormitories of Kashan University of Medical Sciences during the 2013-2014 academic year. A total of 200 students living in the dormitories of Kashan University of Medical Sciences were chosen and examined through simple random sampling, including 100 individuals (50%) with sleep disorders and 100 individuals (50%) without sleep disorders. The data collection tool included demographic information and the Petersburg questionnaire. After entering the EPIINFO software and fixing the bugs and errors, the data were described statistically by the SPSS 16 software, and essential tests such as Chi-square or t-test were employed to examine the relationship between independent and dependent variables. To control confounding variables, relevant regression methods were used. Results: There were 92 boys (46%) and 108 girls (54%) among the students. 22 individuals (11%) were married while 177 individuals (88.5%) were single. The average age of individuals with sleep disorder was 61.22 years, while for those without sleep disorder it was 35.22 years. Which had no significant difference? The most frequent sleeping hours of the participants were related to 24 hours, which were 51 individuals (25.5%). According to statistical tests, there was no relationship between sleep disorders and hours of sleep. (P: 0.287) Conclusion: Sleep quality significantly impacts the health of students. In general, individuals suffering from sleep disorders experienced fewer actual sleep hours compared to those without such disorders, and there was a significant relationship between sleep disorders and actual sleep hours. Focusing on improving the sleep quality of students living in dormitories and implementing needed actions, including awareness and training on sleep hygiene, is essential for improving students’ health outcomes.